Longitudinal Cardiovascular Outcomes of Sleep Disordered Breathing in Children: A Meta-Analysis and Systematic Review. Issue 3 (28th January 2017) - Ehsan, Zarmina; Ishman, Stacey L.; Kimball, Thomas R.; Zhang, Nanhua; Zou, Yuanshu; Amin, Raouf S.
Abstract: Objectives: The presence of sleep disordered breathing (SDB) is known to impact long-term cardiovascular morbidity in adults; however, the long-term effects in children are poorly understood. We aimed to systematically review and synthesize studies published to date on the long-term effects of SDB in children. Study Design: Meta-analysis and systematic review using PubMed, CINAHL, Embase, and Scopus (all indexed years). Methods: We searched for English-language articles containing original human data from prospective studies, with ≥7 participants, in children ≤18 years of age. Data regarding study design, demographics, clinical characteristics, outcomes, level of evidence, and risk of bias were obtained. Articles were independently reviewed by three investigators. Retrospective and cross-sectional studies were excluded. Results: Of 1701 identified abstracts, 25 articles (combined n = 1418) were ultimately included. All studies reported longitudinal outcomes following treatment of SDB, 21 studies exclusively reporting outcomes after adenotonsillectomy. Therefore, studies were combined to objectively assess the effect of SDB treatment on cardiovascular outcomes. Although all cardiovascular parameters were within the normal range at baseline, at follow-up there was a significant decrease in mean pulmonary artery pressure, right ventricular end diastolic diameter, heart rate, mitral Em/Am ratio, and C-reactive protein. There was no significant change in interventricular septum thickness, left ventricular parameters (shortening fraction, systolic and end diastolic diameters, ejection fraction, posterior wall thickness, isovolumetric relaxation time), left atrial diameter, and aortic and pulmonary valve peak velocities. Conclusions: Studies assessing the long-term cardiovascular effects of SDB in children are limited. The available literature indicates effects on autonomic function, right, and left heart function following treatment for SDB. However, well-designed, large-scale, prospective cohort studies (using standardized outcomes) are needed to better understand the relationship of cardiovascular morbidity in the context of pediatric SDB.